A Chain Multiple Mediation Model Linking Strategic, Management, and Technological Innovations to Firm Competitiveness - Chen Han; Shanxing Gao (Revista Brasileira de Gestão De Negócios, 2019)
Purpose – This study attempts to build an integrated framework to discuss the influence of three types of innovations, i.e. strategic, management, and technological innovations, on firm competitiveness. Design/methodology/approach – Paired survey responses are collected from 303 firms located in China. A confirmatory factor analysis is implemented with SPSS AMOS software to check the reliability and validity of all measures through structural equation modeling. Four hypotheses are empirically examined with SPSS PROCESS Macro in combination with a bias-corrected bootstrapping technique to test the chain multiple mediation model linking strategic, management, and technological innovations to firm competitiveness. Findings – Although strategic, management, and technological innovations are carried out at different organizational levels, they formulate a holistic framework to jointly improve firm competitiveness. Strategic innovation strengthens firm competitiveness through three parallel routes, i.e. via management innovation, via technological innovation, and via the serial mediating mechanism of management and technological innovations. Also, the mediation effect of management innovation is significantly stronger than that of technological innovation. Originality/value – This study integrates strategic, management, and technological innovations into the process of improving firm competitiveness to account for their joint influences, challenging the conventional paradigm where different types of innovations are investigated separately. Cross-domain knowledge flow, exchange, and combination are realized within the broad innovation construct.